The Mitochondrial Permeability Transition in Mitochondrial Disorders. (5th May 2019) - Šileikytė, Justina; Forte, Michael
Abstract : Mitochondrial permeability transition pore (PTP), a (patho)physiological phenomenon discovered over 40 years ago, is still not completely understood. PTP activation results in a formation of a nonspecific channel within the inner mitochondrial membrane with an exclusion size of 1.5 kDa. PTP openings can be transient and are thought to serve a physiological role to allow quick Ca 2+ release and/or metabolite exchange between mitochondrial matrix and cytosol or long-lasting openings that are associated with pathological conditions. While matrix Ca 2+ and oxidative stress are crucial in its activation, the consequence of prolonged PTP opening is dissipation of the inner mitochondrial membrane potential, cessation of ATP synthesis, bioenergetic crisis, and cell death—a primary characteristic of mitochondrial disorders. PTP involvement in mitochondrial and cellular demise in a variety of disease paradigms has been long appreciated, yet the exact molecular entity of the PTP and the development of potent and specific PTP inhibitors remain areas of active investigation. In this review, we will (i) summarize recent advances made in elucidating the molecular nature of the PTP focusing on evidence pointing to mitochondrial Fo F1 -ATP synthase, (ii) summarize studies aimed at discovering novel PTP inhibitors, and (iii) review data supporting compromised PTP activity in specific mitochondrial diseases.